PENGARUH UMUR IBU YANG BERESIKO KANKER SERVIKS DAN TINGKAT PENDIDIKAN IBU DENGAN KANKER SERVIKS DI RUANG POLI KANDUNGAN RSUD ULIN BANJARMASIN - Nur Cahyani Ari Lestari; Rima Diaty (Universitas Batam, 2022)
Cervical cancer is first cancer with an estimate every 1 hour a woman dies of cervical cancer in Indonesia, the number of cervical cancers is made worse by the fact that many (70%) cases are already at an advanced stage when they come to the hospital. Based on register data in obstetrics poly Ulin Hospital, Banjarmasin, 68 people were affected by cervical cancer. This study aims to determine age of mothers who are at risk of cervical cancer and level of education of mothers with cervical cancer. This study uses a descriptive method, population is all mothers who checked for cervical cancer in obstetrics poly of RSUD Ulin Banjarmasin totaling 68 people. Sampling with saturated sampling method, namely by taking all the population as a sample. Data collection is taken from data register book. Data processing is summed, tabulated and presented, for further descriptive analysis to determine the age of the mother who is at risk of cervical cancer and the level of education that can affect the occurrence of cervical cancer. The results ,aged over 35 years was 67 people (98.53%) and mothers with cervical cancer with a low level of education (SD) were 36 people (52, 94%). Based on research that has been conducted on 68 mothers who experienced cervical cancer at Ulin Hospital Banjarmasin, it can be concluded that the age of mothers who are at risk for cervical cancer is mostly (> 35 years) and education level of mothers who experienced cervical cancer was mostly (SD).